"What if this is my chance to save my life?" A semistructured interview study on the motives and experiences of end‐stage renal disease patients who engaged in public solicitation of a living kidney donor. (15th December 2017) - Pronk, Mathilde C.; Slaats, Dorthe; Zuidema, Willij C.; Hilhorst, Medard T.; Dor, Frank J. M. F.; Betjes, Michiel; Weimar, Willem; van de Wetering, Jacqueline; Massey, Emma K.
Summary: The increase in patients using public solicitation (PS) to find a living kidney donor has generated a debate about the ethical complexities of PS. To investigate why patients engaged in PS and what they experienced during PS, we conducted semistructured interviews with 20 Dutch patients with end‐stage renal disease who had publicly solicited a living donor. Transcripts were thematically analyzed. We identified ten themes on patients' considerations preceding PS: cautiousness in discussing living donation within social network; reluctance to accept a kidney from loved ones; rejection/withdrawal of related donor candidates; moral objections to paid donation; the ease of social media; encouraged by others; ends justifying the means; despair and urge to take action; public disclosure of vulnerability; fear of being (perceived to be) selfish. We identified nine themes on patients' experiences: positive emotions and support generated by action; genuine and ulterior motives for donation; patients acting as educators and screeners; time‐ and energy‐consuming process; emotionally taxing process; positive interactions with donor candidates; feeling of dependency and obligation; limited cooperation from health professionals; demands a proactive attitude and media strategy. These results can inform and complement (existing) policies on PS and provide content for education of patients who are considering PS.